Mapping Monitoring of Environmental Conditions In Cilacap Waters - Muhamad Kemal Idris; Muqtasidun Hasri; Wahyu Adi Setyaningsih (Politeknik Negeri Batam, 2021)
Cilacap waters are said to be busy with sea traffic with many activities being carried out in the Cilacap water area. Environmental monitoring activities are needed to determine the existing conditions in Cilacap waters, in order to support smooth and efficient traffic activities in Cilacap waters. This study uses a method in producing a mapping of environmental conditions, namely by looking at the aspects of changes in coastline, water depth (bathymetry), wind direction, and velocity, as well as models of surface currents speed and direction in Cilacap waters. The results of this study indicate that the environmental conditions in Cilacap waters are still relatively not much different from the conditions in the previous year, namely 2017. The value of modeling ocean currents which are influenced by sea tides and ebbs has a relatively small value with values ranging from 0.1-1.5 m / s with an average speed of 0.4 m / s that occurs in June (east season). In June 2020 the wind in the Cilacap water area blows from the east and southeast with speeds ranging from 2.5 - 7 m / s. The bathymetry measurement results showed a result of less than -2 meters. These results also indicate a relatively gentle seabed slope with a maximum depth of more than -30 meters in Cilacap waters. This clearly shows that the morphology of the coast and the condition of Cilacap waters are not relatively significant, experiencing changes every year.